Penyuluhan Pencegahan Hipertensi Berbasis Diagnosis Keperawatan Pada Komunitas di Desa Cimandala - Widodo, Wasis; Rochmayanti, Rochmayanti; Wulansari, Novia (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Abstract Introduction: Hypertension is still one of the public health problems in Cimandala. Unhealthy lifestyles are the dominant factor in the triggering of hypertension. Objective: The implementation of the activity was carried out on January 24, 2024, January 29, 2024, and February 6, 2024 which was attended by 26 people. Method: The method used in community service has three stages, namely the first stage is to find priority nursing diagnosis problems in the community and decide on solutions to the problems. The second stage is with intervention and the final stage is with evaluation of the interventions carried out. The implementation of activities in the form of focus group discussions to determine priorities and solutions for village activity programs in collaboration with the health center. Hypertension counseling is carried out with the agreement of all residents. Result: Evaluation of the activity program by distributing pre- and post-test questionnaires, where there was an increase in the score of understanding of hypertension in residents by 25.4. This shows a good number. Conclusion: From the results of these activities, there has been a significant increase, as can be seen from the results of the post-test carried out that residents understand and know more about hypertension, from its definition to its prevention. Healthy lifestyle needs to be encouraged and promoted through various ways, so that people can avoid hypertension Keywords: Nursing Diagnosis, Nursing Intervention and Implementation, Non-Communicable Diseases (Hypertension).